Uji Efektivitas Konsentrasi Kacang Kedelai Sebagai Media Alternatif Terhadap Pertumbuhan Jamur Candida albicans - Rahayu, Putry Shofiyani; Solikah, Monika Putri; Shafriani, Nazula Rahma (Anakes : Jurnal Ilmiah Analis Kesehatan, 2025)
Candida albicans is a type of pathogen fungus that can cause opprtunistic infections, especially in individuals with low immune systems.The gold standard for Candida albicans identification is culture examination using Sabouraud Dextrose Agar (SDA) media, but this is relatively media are needed that are more economical, easily available, and able to support optimal fungal growth. This study aims to determine the effectiveness of soybean (Glycine max) concentration as an alternative media to replace SDA for the growth of Candida albicans. This research was conducted experimentally with a quantitative approach, using a variet of soybean concentrations (5%, 10%, 15%, and 20%) which were tested for growth macrocopically, microscopically (KOH 10% and LPCB), calcualtion of the number of colonies and concentration effectiveness. The results showed that soybean media supported the growth of Candida albicans, with 20%concentration giving effective results resembling growth on SDA media. Based on these results, soybean has the potential as an alternative medium with an economical price for Candida albicans fungal culture in microbiology laboratories.   Keywords: Candida albicans, soybean, alternative media, Sabouraud Dextrose Agar.